Letter to Jane Tolmach from Susie Wilson - Susie Wilson:::::: (1980)
This November 14, 1980 letter from CEWAER President Susanne Wilson reminds Jane Tolmach that her membership renewal is due December 1 and highlights new initiatives for the coming year. The organization plans to establish a permanent central office to strengthen regional meetings, workshops, and networking among elected and professional women across California. The letter emphasizes the importance of member participation and keeping directory information current to maintain CEWAER's effectiveness as a statewide organization.